Sistem Informasi Manajemen Pemasaran dan Penjualan Berbasis Web Menggunakan Content Management System (Cms) Opencart (Studi Kasus Palapa Sablon Romang Lompoa Kabupaten Gowa) - Gunawan; Nahrun Hartono; Evi Sasriani Marsun (Jurnal INSYPRO (Information System and Processing), 2022)
Palapa Sablon is a micro business engaged in convection, especially in serving the manufacture and printing of t-shirts according to customer orders with the number of units or parties. In managing the marketing and sales of products, Palapa Sablon still uses a conventional system where the recording of sales results is done manually or by bookkeeping and does not yet have an official sales website that is used as an information service center to customers or prospective customers which can result in a lack of marketing and product sales management. Based on these problems, researchers use Opencart as a website e-commerce Palapa Sablon. Development and testing methods using Waterfall and System Usability Scale with a sample of 80 respondents.-based Palapa Sablon marketing and sales system web using Opencart resulted in an average SUS score of 74.9. Respondents' assessment of the website is categorized B with a percentile above the average, good (adjective) and acceptable (acceptable), but in terms of NPS it is passive (passive).